An Empirical Appraisal of Canadian Doctoral Dissertations Using Grounded Theory: Implications for Social Work Research and Teaching. Issue 5 (20th October 2017) - Braganza, Morgan; Akesson, Bree; Rothwell, David
ABSTRACT: Grounded theory is a popular methodological approach in social work research, especially by doctoral students conducting qualitative research. The approach, however, is not always used consistently or as originally designed, compromising the quality of the research. The aim of the current study is to assess the quality of recent Canadian social work doctoral dissertations implementing a grounded theory approach. Our analysis is based on the premise that presentations of grounded theory approaches in doctoral dissertations impact the conduct of teaching and future research and have direct implications for the legitimacy of qualitative research. Using Saini and Shlonsky's Qualitative Research Quality Checklist, the authors appraised dissertations in terms of credibility, dependability, confirmability, transferability, authenticity, and relevance. The article concludes with implications regarding the quality of studies utilizing grounded theory approaches and consequences for future doctoral education and research.